Numerical modelling of open-loop ground source energy systems - Cui,W; Gawecka,KA; Potts,DM; Taborda,DMG; Zdravkovic,L (ICE Publishing, 2015)
The environmental and economic benefits of utilising the ground for extracting and storing heat have been known for a long time. However, only recently have government sustainability policies and rising energy prices encouraged the use of this renewable energy resource. In open-loop systems water is abstracted from one well and re-injected into another after exchanging energy with a building’s heating/cooling system using a heat pump. In order to guarantee a good performance of the system, it is fundamental that the possibility of thermal breakthrough occurring is minimised, i.e. that the temperature of the water being abstracted remains unaffected by the injection of warmer/cooler water at the other well. In this paper, the Imperial College FiniteElement Program (ICFEP), which is capable of simulating fully coupled thermo-hydro-mechanical behaviour of porous materials, was used to perform two-dimensional analyses of open-loop ground source heat systems. The parametric studies carried out highlight the relative impact on the occurrence of thermal break-through of the hydraulic ground conditions andthe geometric characteristics of the system, providing an invaluable insight into possible improvements to the current design procedure.